Evaluating the effectiveness of sanitation and hygiene interventions on waterborne diarrheal diseases: A literature review - Tania Asda Jaina; Triana Srisantyorin; Suherman Jaksa (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Waterborne diarrhea remains a major global public health problem closely associated with water quality, sanitation conditions, and hygiene practices. Various interventions have been implemented to reduce the incidence of diarrheal diseases; however, their effectiveness needs to be comprehensively evaluated to provide evidence for environmental health policy and program development. Purpose: To evaluating the effectiveness of sanitation and hygiene interventions on waterborne diarrheal diseases. Method: This study employed a literature review design using a descriptive-analytical approach. Relevant articles were retrieved from Google Scholar, PubMed, ScienceDirect, and nationally accredited SINTA-indexed journals. Articles were selected based on predefined inclusion and exclusion criteria. A total of 10 articles published between 2020 and 2025 were included and analyzed to identify the types of interventions, study findings, and the effectiveness of sanitation and hygiene programs. Results: The findings indicated that all reviewed studies reported a significant association between sanitation and hygiene interventions and a reduction in diarrheal incidence (p< 0.05). Effective interventions included the provision of safe drinking water, the use of improved sanitation facilities, household waste management, handwashing with soap, and integrated Water, Sanitation, and Hygiene (WASH) programs. Integrated WASH interventions demonstrated greater effectiveness than single-component interventions. Conclusion: Sanitation interventions and hygiene practices are effective in reducing the incidence of waterborne diarrheal diseases, particularly when implemented through an integrated WASH approach. Suggestion: Strengthening WASH programs and promoting sustainable behavior change interventions are recommended to support long-term diarrhea prevention efforts.